Diagnosis and classification of autism spectrum disorder - Gleeson, M.B. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
This chapter introduces the evolution of the autism spectrum disorder (ASD) diagnosis. Beginning with the first Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnostic criteria and ending with the current fifth edition (DSM-5) diagnostic criteria, readers will gain an in-depth perspective on changes in ASD diagnostic criteria over time and changes in classification of the disorder. Readers will be provided with an in-depth understanding of the current DSM-5 diagnostic criteria, as well as clinical specifiers and identification of level of support. Discussion is presented on some of the concerns and controversy surrounding the latest diagnostic changes and how those may impact school or support services. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.sed